Il ruolo delle idee e del loro cambiamento nei processi di policy making universitario nel mondo anglosassone dagli anni ottanta ad oggi. I casi di Inghilterra e Nuova Zelanda in prospettiva comparata - De Rosa , Damiano <1978> (Alma Mater Studiorum - Università di Bologna, 2009)
THE TITLE OF MY THESIS IS THE ROLE OF THE IDEAS AND THEIR CHANGE IN HIGHER EDUCATION POLICY-MAKING PROCESSES FROM THE EIGHTIES TO PRESENT-DAY: THE CASES OF ENGLAND AND NEW ZEALAND IN COMPARATIVE PERSPECTIVE UNDER A THEORETICAL POINT OF VIEW, THE AIM OF MY WORK IS TO CARRY OUT A RESEARCH MODELLED ON THE CONSTRUCTIVIST THEORY. IT FOCUSES ON THE ANALYSIS OF THE IMPACT OF IDEAS ON THE PROCESSES OF POLICY MAKING BY MEANS OF EPISTEMIC COMMUNITIES, THINK TANKS AND VARIOUS SOCIOECONOMIC CONTEXTS THAT MAY HAVE PLAYED A KEY ROLE IN THE CONSTRUCTION OF THE DIFFERENT PATHS. FROM MY POINT OF VIEW IDEAS CONSTITUTE A PRIORITY RESEARCH FIELD WHICH IS WORTH ANALYSING SINCE THEIR ROLE IN POLICY MAKING PROCESSES HAS BEEN TRADITIONALLY RATHER UNEXPLORED. IN THIS CONTEXT AND WITH THE AIM OF DEVELOPING A RESEARCH STRAND BASED ON THE ROLE OF IDEAS, I INTEND TO CARRY ON MY STUDY UNDER THE PERSPECTIVE OF CHANGE. DEPENDING ON THE DATA AND INFORMATION THAT I COLLECTED I EVALUATED THE WEIGHT OF EACH OF THESE VARIABLES AND MAYBE OTHERS SUCH AS THE INSTITUTIONS AND THE INDIVIDUAL INTERESTS, WHICH MAY HAVE INFLUENCED THE FORMATION OF THE POLICY MAKING PROCESSES. UNDER THIS LIGHT, I PLANNED TO ADOPT THE QUALITATIVE METHODOLOGY OF RESEARCH WHICH I BELIEVE TO BE VERY EFFECTIVE AGAINST THE MORE DIFFICULT AND POSSIBLY REDUCTIVE APPLICATION OF QUANTITIVE DATA SETS. I RECKON THEREFORE THAT THE MOST APPROPRIATE TOOLS FOR INFORMATION PROCESSING INCLUDE CONTENT ANALYSIS, AND IN-DEPTH INTERVIEWS TO PERSONALITIES OF THE POLITICAL PANORAMA (ÉLITE OR NOT) WHO HAVE PARTICIPATED IN THE PROCESS OF HIGHER EDUCATION REFORM FROM THE EIGHTIES TO PRESENT-DAY. THE TWO CASES TAKEN INTO CONSIDERATION SURELY SET AN EXAMPLE OF RADICAL REFORM PROCESSES WHICH HAVE OCCURRED IN QUITE DIFFERENT CONTEXTS DETERMINED BY THE SOCIOECONOMIC CHARACTERISTICS AND THE TRAITS OF THE ÉLITE. IN NEW ZEALAND THE DESCRIBED PROCESS HAS TAKEN PLACE WITH A STEADY PACE AND A GOOD GRADE OF CONSEQUANTIALITY, IN LINE WTH THE REFORMS IN OTHER STATE DIVISIONS DRIVEN BY THE IDEAS OF THE NEW PUBLIC MANAGEMENT. CONTRARILY IN ENGLAND THE REFORMATIVE ACTION OF MARGARET THATCHER HAS ACQUIRED A VERY RADICAL CONNOTATION AS IT HAS BROUGHT INTO THE AMBIT OF HIGHER EDUCATION POLICY CONCEPTS LIKE EFFICIENCY, EXCELLENCE, RATIONALIZATION THAT WOULD CONTRAST WITH THE GENERALISTIC AND MASS-ORIENTED IDEAS THAT WERE FASHIONABLE DURING THE SEVENTIES. THE MISSION I INTEND TO ACCOMPLISH THORUGHOUT MY RESEARCH IS TO INVESTIGATE AND ANALYSE INTO MORE DEPTH THE DIFFERENCES THAT SEEM TO EMERGE FROM TWO CONTEXTS WHICH MOST OF THE LITERATURE REGARDS AS A SINGLE MODEL: THE ANGLO-SAXON MODEL. UNDER THIS LIGHT, THE DENSE ANALYSIS OF POLICY PROCESSES ALLOWED TO BRING OUT BOTH THE CONTROVERSIAL AND CONTRASTING ASPECTS OF THE TWO REALITIES COMPARED, AND THE ROLE AND WEIGHT OF VARIABLES SUCH AS IDEAS (MAIN VARIABLE), INSTITUTIONAL SETTINGS AND INDIVIDUAL INTERESTS ACTING IN EACH CONTEXT. THE CASES I MEAN TO ATTEND PRESENT PECULIAR ASPECTS WORTH DEVELOPING AN IN-DEPTH ANALYSIS, AN OUTLINE OF WHICH WILL BE PROVIDED IN THIS ABSTRACT. ENGLAND THE CONSERVATIVE GOVERNMENT, SINCE 1981, INTRODUCED RADICAL CHANGES IN THE SECTOR OF HIGHER EDUCATION: FIRST CUTTING DOWN ON STATE FUNDINGS AND THEN WITH THE CREATION OF AN INSTITUTION FOR THE PLANNING AND LEADERSHIP OF THE POLYTECHNICS (NON-UNIVERSITY SECTOR). AFTERWARDS THE SCHOOL REFORM BY MARGARET THATCHER IN 1988 RAISED TO A GREAT STIR ALL OVER EUROPE DUE TO BOTH ITS CONSIDERABLE INNOVATIVE IMPRINT AND THE STRONG ATTACK AGAINST THE PEDAGOGY OF THE ‘ACTIVE’ SCHOOLING AND PROGRESSIVE EDUCATION, UNTIL THEN RECOGNIZED AS A MERIT OF THE BRITISH PUBLIC SCHOOL. IN THE AMBIT OF UNIVERSITY EDUCATION THIS REFORM, TOGETHER WITH SIMILAR MEASURES BROUGHT IN DURING 1992, PUT INTO PRACTICE THE CONSERVATIVE PRINCIPLES THROUGH A SERIES OF ACTIONS THAT INCLUDED: THE SUPPRESSION OF THE IRREMOVABILITY PRINCIPLE FOR UNIVERSITY TEACHERS; THE INTRODUCTION OF STUDENT LOANS FOR LOW-INCOME STUDENTS AND THE CANCELLATION OF THE CLEAR DISTINCTION BETWEEN UNIVERSITIES AND POLYTECHNICS. THE POLICIES OF THE LABOUR MAJORITY OF MR BLAIR DID NOT QUITE DIVERGE FROM THE CONSERVATIVES’ POSITION. IN 2003 BLAIR’S CABINET RISKED TO BECOME A MINORITY RIGHT ON THE OCCASION OF AN IMPORTANT UNIVERSITY REFORM PROPOSAL. THIS PROPOSAL WOULD FORESEE THE AUTONOMY FOR THE UNIVERSITIES TO RAISE UP TO 3.000 POUNDS THE ENROLMENT FEES FOR STUDENTS (WHILE FORMERLY THE CEILING WAS 1.125 POUNDS). BLAIR HAD TO FACE INTERNAL OPPOSITION WITHIN HIS OWN PARTY IN RELATION TO A MEASURE THAT, ACCORDING TO THE 150 MPS PROMOTERS OF AN ADVERSE MOTION, HAD NOT BEEN INCLUDED IN THE ELECTORAL PROGRAMME AND WOULD RISK CREATING INCOME-BASED DISCRIMINATION AMONG STUDENTS. AS A MATTER OF FACT THE BILL FOCUSED ON THE INTRODUCTION OF VERY LOW-INTEREST STUDENT LOANS TO BE SETTLED ONLY WHEN THE STUDENT WOULD HAVE FOUND A REMUNERATED OCCUPATION (A SYSTEM ALREADY PROVIDED FOR BY THE AUSTRALIAN LEGISLATION). NEW ZEALAND CONTRARILY TO MANY OTHER COUNTRIES, NEW ZEALAND HAS ADOPTED A VERY WIDE VISION OF THE TERTIARY EDUCATION. IT INCLUDES IN FACT THE FULL EDUCATIONAL PROGRAMME THAT IS INTERNATIONALLY RECOGNIZED AS THE POST-SECONDARY EDUCATION. SHOULD WE SPOTLIGHT A PECULIARITY OF THE NEW ZEALAND TERTIARY EDUCATION POLICY THEN IT WOULD BE ‘CHANGE’. LOOKING AT THE REFORM HISTORY RELATED TO THE TERTIARY EDUCATION SYSTEM, WE CAN CLEARLY IDENTIFY FOUR ‘SUB-PERIODS’ FROM THE EIGHTIES TO PRESENT-DAY: 1. BEFORE THE 80S’: AN ELITARIAN SYSTEM CHARACTERIZED BY LOW PARTICIPATION RATES. 2. BETWEEN MID AND LATE 80S’: A TREND TOWARDS THE ENLARGEMENT OF PARTICIPATION ASSOCIATED TO A GREATER COMPETITION. 3. 1990-1999: A FUTHER STEP TOWARDS A COMPETITIVE MODEL BASED ON THE MARKET-ORIENTED SYSTEM. 4. FROM 2000 TO TODAY: A CONTINUOUS EVOLUTION TOWARDS A MORE COMPETITIVE MODEL BASED ON THE MARKET-ORIENTED SYSTEM TOGETHER WITH A GROWING ATTENTION TO STATE CONTROL FOR SOCIAL AND ECONOMIC DEVELOPMENT OF THE NATION. AT PRESENT THE GOVERNMENT OF NEW ZEALAND OPERATES TO STRENGHTHEN THIS PROCESS, PRIMARILY IN RELATION TO THE ROLE OF TERTIARY EDUCATION AS A STEADY FACTOR OF NATIONAL WALFARE, WHERE PROFESSIONAL DEVELOPMENT CONTRIBUTES ACTIVELY TO THE GROWTH OF THE NATIONAL ECONOMIC SYSTEM5. THE CASES OF ENGLAND AND NEW ZEALAND ARE THE FOCUS OF AN IN-DEPTH INVESTIGATION THAT STARTS FROM AN ANALYSIS OF THE POLICIES OF EACH NATION AND DEVELOP INTO A COMPARATIVE STUDY. AT THIS POINT I ATTEMPT TO DRAW SOME PRELIMINARY IMPRESSIONS ON THE FACTS ESSENTIALLY DECRIBED ABOVE. THE UNIVERSITY POLICIES IN ENGLAND AND NEW ZEALAND HAVE BOTH UNDERGONE A SIGNIFICANT REFORMATORY PROCESS SINCE THE EARLY EIGHTIES; IN BOTH CONTEXTS THE IMPORTANCE OF IDEAS THAT CONSTITUTED THE BASE OF POLITICS UNTIL 1980 WAS QUITE RELEVANT. GENERALLY SPEAKING, IN BOTH CASES THE PRE-REFORM POLICIES WERE INSPIRED BY EGALITARIANISM AND EXPANSION OF THE STUDENT POPULATION WHILE THOSE BROUGHT IN BY THE REFORM WOULD PURSUE EFFICIENCY, QUALITY AND COMPETITIVENESS. UNDOUBTEDLY, IN LINE WITH THIS GENERAL TENDENCY THAT REFLECTS THE HYPOTHESIS PROPOSED, THE TWO UNIVERSITY SYSTEMS PRESENT SEVERAL DIFFERENCES. THE UNIVERSITY SYSTEM IN NEW ZEALAND PROCEEDED STEADILY TOWARDS THE IMPLEMENTATION OF A MANAGERIAL CONCEPTION OF TERTIARY EDUCATION, ESPECIALLY FROM 1996 ONWARDS, IN ACCORDANCE WITH THE REFORMATORY PROCESS OF THE WHOLE PUBLIC SECTOR. IN THE UNITED KINGDOM, AS IN THE REST OF EUROPE, THE NEW APPROACH TO UNIVERSITY POLICY-MAKING HAD TO CONFRONT A DEEP-ROOTED TRADITION OF PROGRESSIVE EDUCATION AND THE IDEA OF EDUCATION EXPANSION THAT IN FACT DOMINATED UNTIL THE EIGHTIES. FROM THIS VIEW POINT THE GOVERNING ACTION OF MARGARET THATCHER GAVE RISE TO A RADICAL CHANGE THAT REVOLUTIONIZED THE OBJECTIVES AND KEY VALUES OF THE WHOLE EDUCATIONAL SYSTEM, IN PARTICULAR IN THE HIGHER EDUCATION SECTOR. IDEAS AS EFFICIENCY, EXCELLENCE AND CONTROL OF THE PERFORMANCE BECAME DECISIVE. THE LABOUR CABINETS OF BLAIR DEVELOPED IN THE WAKE OF CONSERVATIVE REFORMS. THIS APPEARS TO BE A FOCAL POINT OF THIS STUDY THAT OBSERVES HOW ALSO IN NEW ZEALAND THE REFORMING PROCESS OCCURRED TRANSVERSELY DURING PROGRESSIVE AND CONSERVATIVE ADMINISTRATIONS. THE PRELIMINARY IMPRESSION IS THEREFORE THAT IDEAS DEEPLY MARK THE REFORMATIVE PROCESSES: THE AIM OF MY RESEARCH IS TO VERIFY TO WHICH EXTENT THIS STATEMENT IS TRUE. IN ORDER TO BUILD A COMPREHENSIVE ANALYLIS, FURTHER SIGNIFICANT FACTORS WILL HAVE TO BE INVESTIGATED: THE WAY IDEAS ARE PERCEIVED AND IMPLEMENTED BY THE DIFFERENT POLITICAL ELITES; HOW THE VARIOUS SOCIOECONOMIC CONTEXTS INFLUENCE THE REFORMATIVE PROCESS; HOW THE INSTITUTIONAL STRUCTURES CONDITION THE POLICY-MAKING PROCESSES; WHETHER INDIVIDUAL INTERESTS PLAY A ROLE AND, IF YES, TO WHICH EXTENT.